Biomonitoring with Organism Traits and Impacts of SmallImpoundments on Stream Ecological Integrity and FoodWeb - Mbaka, John Gichimu (My University, 2015)
Change of ecosystems and the associated loss of biodiversity is among the most important environmental issues. Climate change, pollution, and impoundments are considered as major drivers of biodiversity loss. Organism traits are an appealing tool for the assessment of these three stressors, due to their ability to provide mechanistic links between organism responses andstressors, and consistency over wide geographical areas. Additionally, traits such as feedinghabits influence organismal performance and ecosystem processes. Although the response of traits of specific taxonomic groups to stressors is known, little is known about the response oftraits of different taxonomic groups to stressors. Additionally, little is known about the effects of small impoundments on stream ecosystem processes, such as leaf litter decomposition, and foodwebs. After briefly introducing the theoretical background and objectives of the studies, this thesis begins by synthesizing the responses of traits of different taxonomic groups to climate change and pollution. Based on 558 peer-reviewed studies, the uniformity (i.e., convergence) intrait response across taxonomic groups was evaluated through meta-analysis (Chapter 2).Convergence was primarily limited to traits related to tolerance. In Chapter 3, the hypothesis thatsmall impoundments would modify leaf litter decomposition rates at the sites located within thevicinity of impoundments, by altering habitat variables and invertebrate functional feeding groups (FFGs) (i.e., shredders), was tested. Leaf litter decomposition rates were significantly reduced at the study sites located immediately upstream (IU) of impoundments, and were significantly related to the abundance of invertebrate shredders. In Chapter 4, the invertebrateFFGs were used to evaluate the effect of small impoundments on stream ecosystem attributes.The results showed that heterotrophic production was significantly reduced at the sites IU. With regard to food webs, the contribution of methane gas derived carbon to the biomass ofiii chironomid larvae was evaluated through correlation of stable carbon isotope values of chironomid larvae and methane gas concentrations. The results indicated that the contribution ofmethane gas derived carbon into stream benthic food web is low. In conclusion, traits are a useful tool in detecting ecological responses to stressors across taxonomic groups, and the effects of small impoundments on stream ecological integrity and food web are limited.